The rôle of second opinion in oncology: an update - Wunsch, Alessia; Palmieri, Beniamino (European Journal of Oncology and Environmental Health, 2014)
It has been demonstrated that second opinion (SO) in medicine and surgery may influence the diagnosis, as well as treatment and prognosis; in fact, the patient may achieve treatment optimization and avoid unnecessary risks and costs. Most of the studies reviewed in this editorial evaluated the benefits of second opinions and the reasons on which the patients seek a medical SO in oncology. SOs are, in fact, pretty common in cancer care with most patients motivated by the need for improved communication, additional information and reassurance. Also the Web has become a relevant partner in this procedure, but to avoid the unpleasant “Web Babel Syndrome”, it is necessary an easy access to SO consulting medical offices.